Dentin phosphoprotein frameshift mutations in hereditary dentin disorders and their variation patterns in normal human population. Issue 7 (2nd May 2008) - Song, Y L; Wang, C N; Fan, M W; Su, B; Bian, Z
Abstract : Background: Dentin phosphoprotein (DPP) is the most abundant non-collagenous protein in dentin, which is highly phosphorylated and plays key roles in dentin biomineralisation. The aetiology of isolated hereditary dentin disorders in most affected families is largely unknown and the association between DPP and dentin disorders has not been well established. This study aims to determine whether there are some involvements for DPP mutations in inherited dentin disorders and to clarify the sequence variation patterns of DPP in normal population. Methods: Genomic DNA was analysed in eight families with hereditary dentin disorders and 110 individuals in the normal population. The full coding sequence of DPP was amplified by polymerase chain reaction (PCR) and screened for mutations and variations by direct sequencing and TOPO TA-cloning sequencing. Results: Five frameshift mutations in DPP coding region were identified in five of the eight families. The mutations co-segregated with the disease phenotypes in affected families and were not found in 220 control chromosomes. In the normal population, we revealed 14 in-frame indels (insertion/deletion), six non-synonymous single nucleotide polymorphisms (SNPs), and five synonymous SNPs in the DPP coding region. These variants display extensive linkage disequilibrium and constitute a total of 15 haplotypes with three predominant haplotypes in the investigated normal population. Conclusions: Our data provide the first evidence that DPP mutations can cause hereditary dentin disorders and suggest that in-frame length variations and missense SNPs in DPP have no obvious pathogenetic effects on dentin formation.